2017
DOI: 10.1002/adfm.201703019
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Effects on the Electrochemical Stimulation Performance of Au, Pt, and PEDOT:PSS Electrocorticography Arrays

Abstract: The efficacy of electrical brain stimulation in combatting neurodegenerative diseases and initiating function is expected to be significantly enhanced with the development of smaller scale microstimulation electrodes and refined stimulation protocols. These benefits cannot be realized without a thorough understanding of scaling effects on electrochemical charge injection charac teristics. This study fabricates and characterizes the electrochemical stimu lation capabilities of Au, Pt, poly(3,4ethylenedioxythiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 36 publications
4
82
0
Order By: Relevance
“…The platform consisted of a polyvinyl alcohol (PVA) sponge which was implanted subcutaneously at the wound site. [22,23] As prior meta-studies [6,8,11] show that there is ongoing debate over the types of ES parameters necessary for wound treatment, the magnitude and frequency of ES waveforms were varied here to examine their effects on immune cells in mice wound models. [15][16][17][18] Using subcutaneous implants of PVA sponges, we are able to establish data in animal models that can be measured in a laboratory setting.…”
Section: Doi: 101002/adbi201900106mentioning
confidence: 99%
See 4 more Smart Citations
“…The platform consisted of a polyvinyl alcohol (PVA) sponge which was implanted subcutaneously at the wound site. [22,23] As prior meta-studies [6,8,11] show that there is ongoing debate over the types of ES parameters necessary for wound treatment, the magnitude and frequency of ES waveforms were varied here to examine their effects on immune cells in mice wound models. [15][16][17][18] Using subcutaneous implants of PVA sponges, we are able to establish data in animal models that can be measured in a laboratory setting.…”
Section: Doi: 101002/adbi201900106mentioning
confidence: 99%
“…The finer patterning capability of the inkjet printing process allows for rapid prototyping and fabrication of high-density arrays. [22,23] As shown in Figure our ES studies comparing the effects of applied current amplitudes and frequencies, as shown in the table of Figure 1C. We used hydrogel phantoms to create areas of low and high impedance and measured the impedance magnitude and phase angle between pairs of neighboring electrodes.…”
Section: Doi: 101002/adbi201900106mentioning
confidence: 99%
See 3 more Smart Citations